Gamelan Recordings As an Archive of the Gamelan Music Movement in Bali | Rekaman Gamelan sebagai Arsip Pergerakan Musik Gamelan di Bali - Raditya, I Gusti Putu Agung Raditya Utara (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
This article reviews the role of Gamelan recordings as archives in documenting the movement of Gamelan music in Bali. The research was conducted through observation and interviews to understand the practices and outcomes of using recordings in the Balinese cultural context. Through direct observation and interviews, this study explored various developments in playing techniques, styles, and composition forms. Recording is a process of capturing sound or images stored in digital or analogue format, serving as archives for work documentation, reproduction, and distribution. An archive consists of various documents, records, or other items stored for historical or administrative purposes. Archives may include written, audio, visual, or digital recordings encapsulating essential or valuable information in specific texts and contexts such as history, culture, and law. Thus, combining research methods has yielded a profound understanding of how recordings function as archives of the Gamelan music movement in Bali and have added value to the preservation and development of traditional culture. Furthermore, this article provides deep insights into how Gamelan recordings can be valuable in understanding the evolution of traditional Balinese music.